Accessing ICT for science teaching in Nigerian schools: whither the role of school library media centre? (2015)
Aim: This study investigated ICT usage and the role of SLMCs in Federal Unity Schools in Nigeria in facilitating the usage of ICT by science teachers in Nigeria. Study Design: Survey research design was adopted for the study. Four instruments were used. Methodology: Multistage sampling technique was adopted. Systematic sampling technique was used in selecting the schools for the study while the census technique was used in selecting the respondents. Four research instruments viz: ICT Availability scale (r=0.72), ICT Accessibility scale (r=0.83), ICT Usage (r=0.89) and Role of SLMC Scale (0.75) were used in collecting data. These were complemented with observation checklist. Three research questions were answered. Location of the Study: Science teachers in selected 25 Federal Unity Schools in Nigeria were chosen for the study. Findings: The study revealed low usage of science-based ICT facilities, low level of science-based ICT availability and accessibility as well as poor role of SLMCs in facilitating ICT usage among science teachers in FUSs in Nigeria. Recommendations: The SLMC should be adequately equipped so as to function effectively in providing support efficient ICT usage by science teachers in Nigeria.